1997
DOI: 10.1098/rspb.1997.0035
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting levels of variability between cytoplasmic genomes and incompatibility types in the mosquitoCulex pipiens

Abstract: SUMMARYReproductive incompatibilities called cytoplasmic incompatibilities are known to affect a large number of arthropod species and are mediated by Wolbachia, a maternally transmitted microorganism. The crossing relationships between strains of potential hosts define their incompatibility types and it is generally assumed that differences between strains of Wolbachia induce different crossing types. Among all the described host species, the mosquito, ulex pipiens, displays the greatest variability of cytopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
109
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(117 citation statements)
references
References 63 publications
6
109
1
1
Order By: Relevance
“…quinquefasciatus and Cx. pipiens mitochondrial genes has been reported by GUILLEMAUD et al 17 . HASAN et al 18 also found low diversity (Hd = 0.502 and π = 0.0007) in the Cx.…”
Section: Discussionmentioning
confidence: 86%
“…quinquefasciatus and Cx. pipiens mitochondrial genes has been reported by GUILLEMAUD et al 17 . HASAN et al 18 also found low diversity (Hd = 0.502 and π = 0.0007) in the Cx.…”
Section: Discussionmentioning
confidence: 86%
“…Barriol and Mart, which displayed identical compatibility towards the other strains, differed from six markers indicating that distinct Wolbachia strains thus do not necessarily generate CI. Matching WO polymorphism to the CI pattern reported in Guillemaud et al (1997) failed to show a correlation, except for Gp15. All crosses between Gp15a strains (Barriol, Espro and Mart, table 3) were fully compatible bi-directionnally.…”
Section: Results (A)mentioning
confidence: 94%
“…This notion was strengthened by the lack of congruence between Wolbachia and phage phylogenies established with the orf7 sequence (ORF Gp3 in our study), suggesting horizontal phage exchange between bacteria co-infecting the same intracellular environment (Bordenstein & Wernegreen 2004;Gavotte et al 2004;Sanogo & Dobson 2004). Since all polymorphic regions found so far in wPip DNA are mobile genetic elements (Sanogo & Dobson 2004;Duron et al 2005), the 'real' Wolbachia genes being monomorphic (Rousset et al 1992;Guillemaud et al 1997;Duron et al 2005), it was proposed that these mobile genetic elements could favour genome fluidity and enhance rapid adaptation, especially in the highly diversified CI system of C. pipiens. For all these reasons we decided to study WO prophage organization and variability in the wPip genome.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations